2015
DOI: 10.1080/19336896.2015.1025189
|View full text |Cite
|
Sign up to set email alerts
|

Prion aggregates transfer through tunneling nanotubes in endocytic vesicles

Abstract: ABSTRACT. Transmissible spongiform encephalopathies (TSEs) are a group of neurodegenerative diseases caused by the misfolding of the cellular prion protein to an infectious form PrP Sc . The intercellular transfer of PrP Sc is a question of immediate interest as the cell-to-cell movement of the infectious particle causes the inexorable propagation of disease. We have previously identified tunneling nanotubes (TNTs) as one mechanism by which PrP Sc can move between cells. Here we investigate further the details… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 37 publications
(52 reference statements)
5
74
0
Order By: Relevance
“…In the co-culture system used here, we observed no transmission by supernatant or in the condition of co-culture filter, indicating that the intercellular transfer of DISC1 aggregates is not mediated by secretion and requires cell-to-cell contact. As previously shown for prion and other proteins involved in neurodegenerative diseases [29,30,38,39,56,57], we found that DISC1 aggregates can also transfer between cells through TNTs. This was also supported by the finding that the efficiency of transfer was increased upon induction of TNT formation by Myo10, a positive regulator of TNTs, and reduced by VASP, a negative regulator of TNTs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the co-culture system used here, we observed no transmission by supernatant or in the condition of co-culture filter, indicating that the intercellular transfer of DISC1 aggregates is not mediated by secretion and requires cell-to-cell contact. As previously shown for prion and other proteins involved in neurodegenerative diseases [29,30,38,39,56,57], we found that DISC1 aggregates can also transfer between cells through TNTs. This was also supported by the finding that the efficiency of transfer was increased upon induction of TNT formation by Myo10, a positive regulator of TNTs, and reduced by VASP, a negative regulator of TNTs.…”
Section: Discussionsupporting
confidence: 86%
“…Compared to proteins related to neurodegenerative diseases, the efficiency of transfer of DISC1 aggregates is lower [29,30,56,58,59]. The inefficient transmission of DISC1 aggregates may be due to the low cell invasiveness and limited movement of these aggregates as previously reported [17,42].…”
Section: Discussionmentioning
confidence: 91%
“…TNTs are also emerging as an important player in cancer development561213. We have previously demonstrated that TNTs can mediate the intercellular transfer of infectious prions between neuronal cells, dendritic cells to neurons, and between astrocytes14151617. Interestingly, other “prion-like” amyloidogenic proteins like misfolded huntingtin18, amyloid β19, α-synuclein20, and tau21 can also be transferred between distant cells through TNTs, thus underscoring the important role of TNTs in the progression of neurodegenerative diseases, and their potential use as therapeutic targets22.…”
mentioning
confidence: 99%
“…First, pathogens such as viruses (Sowinski et al, 2008;Hashimoto et al, 2016;Kumar et al, 2017;Panasiuk et al, 2018) and bacteria (Önfelt et al, 2006;Kim et al, 2019) can use IMTs as a means of cell-to-cell transfer. Second, mis-folded protein aggregates including huntingtin (Costanzo et al, 2013), prion protein (Zhu et al, 2015), and -synuclein (Abounit et al, 2016) have also been shown to transfer between cells through IMTs. Finally, IMTs have been linked to increased treatment resistance of several cancers.…”
Section: Introductionmentioning
confidence: 99%